Popular grievances in the Arab region: evaluating explanations for discontent in the lead-up to the uprisings. Issue 1 (2nd January 2018) - Cammett, Melani; Salti, Nisreen
ABSTRACT: In the wake of the Arab uprisings, analysts have advanced multiple hypotheses about the grievances at the root of mass mobilization, yet little empirical research examines their validity, particularly at the micro-level. We use survey data from 2009 to 2010 from Arab countries that experienced mass protests to assess the validity of dominant approaches. Cross-national variation in patterns of grievances lends support to claims that diffusion processes rather than a common set of concerns fuelled the uprisings.